Predator control promotes invasive dominated ecological states - A Wallach; C Johnson; Euan Ritchie; A O'Neill (2010)
Invasive species are regarded as one of the top five drivers of the global extinction crisis. In response, extreme measures have been applied in an attempt to control or eradicate invasives, with little success overall. We tested the idea that state shifts to invasive dominance are symptomatic of losses in ecosystem resilience, due to the suppression of apex predators. This concept was investigated in Australia where the high rate of mammalian extinctions is largely attributed to the destructive influence of invasive species. Intensive pest control is widely applied across the continent, simultaneously eliminating Australia’s apex predator, the dingo (Canis lupus dingo). We show that predator management accounts for shifts between two main ecosystem states. Lethal control fractures dingo social structure and leads to bottom-up driven increases in invasive mesopredators and herbivores. Where control is relaxed, dingoes re-establish top–down regulation of ecosystems, allowing for the recovery of biodiversity and productivity.